Examen especial a las operaciones administrativas y financieras en el GAD parroquial La Magdalena, cantón Chimbo, provincia Bolívar, período 2022-2023. - Arevalo Cayambe, Yuliana Mirella (2025)
This project focused on carrying out a Special Examination of the administrative and financial operations of the La Magdalena Parish GAD, in the Chimbo canton, Bolívar province, during the period 2022-2023, with the purpose of demonstrating how the examination can strengthen said operations, improving internal controls and ensuring compliance with regulations. To achieve this, the aim was to identify weaknesses and risks that have affected the efficiency and effectiveness in the management of public resources in these two periods; in the research process, a visit was made to the institution, which revealed the lack of intervention by the General Comptroller of the State from 2010 to 2014. For this research, methodologies were applied, including the deductive method, which starts from the general to the specific, and the descriptive method, which allows a more in-depth analysis of the data, instruments such as surveys and interviews were used to evaluate the degree of knowledge about the administrative and financial activities of the institution. During these evaluations, it was found that the operational staff does not have knowledge about these activities; this is why the survey was carried out on the inhabitants of the parish in order to gather relevant information about the administrative and financial operations carried out by the entity. In conclusion, the examination is not only an evaluation mechanism, but also an opportunity to promote positive change; this ensures that officials are aligned with institutional objectives, thus promoting a more efficient and transparent public administration.